Generative AI Adoption in Indonesian Higher Education: A Sociotechnical Analysis of Student Engagement, Digital and AI Literacy, and Academic Integrity - Sudrajat Sudrajat; Bagaskara Nur Rochmansyah; Leonita Leonita; Zhou Yin Lin; Syahrul Anwar (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
Generative artificial intelligence (GenAI) has rapidly entered higher education and changed how students access information, complete academic tasks, and engage with learning. However, GenAI adoption cannot be understood only as individual technology use because it is also shaped by literacy, academic integrity, institutional rules, and pedagogical context. This study analyzes GenAI adoption in Indonesian higher education through a sociotechnical perspective. The study used a descriptive-analytical design based on an Indonesian higher education subset extracted from a public global survey dataset on students’ early perceptions of ChatGPT. After institutional-location filtering, the final analytical subset consisted of 270 respondents affiliated with higher education institutions located in Indonesia. The analysis focused on GenAI adoption, technology acceptance, digital and AI literacy, student engagement, academic integrity, and institutional support. The findings show that students demonstrated more favorable satisfaction and attitude scores than usage-frequency scores, indicating that positive perceptions of ChatGPT did not automatically translate into intensive academic use. The study also found that digital and AI literacy is a key condition for responsible GenAI adoption because students need to evaluate AI-generated outputs, recognize limitations, verify information, and apply ethical judgment. Study-related outcome blocks showed moderate-to-positive tendencies, suggesting that ChatGPT may support learning, although its contribution to engagement remains developing. Regulation and ethical concern blocks also showed moderate awareness but continuing uncertainty regarding acceptable use. The study concludes that responsible GenAI adoption in Indonesian higher education requires balanced institutional guidance, AI literacy development, assessment redesign, and clear academic integrity policies.